Transcriptomic Drivers of Differentiation, Maturation, and Polyploidy in Human Extravillous Trophoblast - Morey, Robert; Farah, Omar; Kallol, Sampada; Requena, Daniela F.; Meads, Morgan; Moretto-Zita, Matteo; Soncin, Francesca; Laurent, Louise C.; Parast, Mana M. (Frontiers in Cell and Developmental Biology, 2021)
During pregnancy, conceptus-derived extravillous trophoblast (EVT) invade the endomyometrium, anchoring the placenta to the maternal uterus, and remodel the spiral arteries in order to establish maternal blood supply to the fetoplacental unit. Recent reports have described early gestation EVT as polyploid and senescent. Here we extend these reports by performing comprehensive profiling of both the genomic organization and transcriptome of first trimester and term EVT. We define pathways and gene regulatory networks involved in both initial differentiation and maturation of this important trophoblast lineage at the maternal-fetal interface. Our results suggest that like first trimester EVT, term EVT undergo senescence and endoreduplication, are primarily tetraploid, and lack high rates of copy number variations. Additionally, we have highlighted senescence and polyploidy-related genes, pathways, networks, and transcription factors that appeared to be important in normal EVT differentiation and maturation and validated a key role for the unfolded protein response in this context.